Gross Anatomical and Morphometrical Studies on Humerus of Civet Cat (Viverricula indica) - Kamal Sarma,; Shalini Suri,; Jasvinder Singh Sasan, (Indian Journal of Veterinary Anatomy, 2024)
Humerus of civet cat was a long bone with spirally twisted shaft and two prominent extremities. Proximal extremity consisted of a smooth, spherical head which was placed postero-medially. Lesser tuberosity was present medial to head whereas greater tuberosity was placed lateral to head. Anteriorly, lesser and greater tuberosities were separated by a wide bicipital groove with centrally placed tubercle. On the postero-lateral aspect of greater tuberosity a distinct circular area for infra-spinatus muscle was present. Distal extremity consisted of a pair of prominent condyles, shallow coronoid and radial fossae on cranial aspect. Condyles consisted of a large medial trochlea and a small lateral capitulum. Trochlea presented unequal lips. Coronoid fossa was observed proximal to trochlea whereas radial fossa was located proximal to capitulum. Just proximal to medial epicondyle a very conspicuous ovoid slit-like passage known as supra-condyloid foramen was present. Supra-trochlear foramen was observed. Proximal half of the shaft presented a medial pectoral ridge and lateral deltoid ridge. Distally, a sharp ridge extended from the lateral epicondyle posteriorly to about the middle of the shaft. The nutrient foramen was present on the medial surface of the distal 3rd of the shaft.